Organization of training of future specialists in sports and physical culture - Horbatiuk N., Sovhira S., Karasievych S., Boiko Y., Tanasiichuk Y., (Opción, 2019)
The aim of the study is to theoretically substantiate and experimentally test the organizational and methodological support of physical culture and sports training of future specialists via theoretical, empirical and statistical methods. In result, in the experimental groups, the high level of readiness of future specialists of physical culture and sports for physical culture and sports activities increased by 16.5 % compared to the ascertaining stage; medium-level − by 24.3 %. In conclusion, there is a change in the levels of readiness of future specialists from the experimental group for physical culture and sports activities from low to high.